2013
DOI: 10.1152/ajpregu.00099.2013
|View full text |Cite
|
Sign up to set email alerts
|

Central administration of metformin into the third ventricle of C57BL/6 mice decreases meal size and number and activates hypothalamic S6 kinase

Abstract: Kim HJ, Park EY, Oh MJ, Park SS, Shin KH, Choi SH, Chun BG, Kim DH. Central administration of metformin into the third ventricle of C57BL/6 mice decreases meal size and number and activates hypothalamic S6 kinase. Am J Physiol Regul Integr Comp Physiol 305: R499 -R505, 2013. First published July 3, 2013 doi:10.1152/ajpregu.00099.2013.-Administration of metformin is known to reduce both body weight and food intake. Although the hypothalamus is recognized as a critical regulator of energy balance and body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…In these experiments we present surprising evidence suggesting that metformin increases mTORC1 signaling in embryonic pancreata. This positive effect of metformin has been recently demonstrated in hypothalamic tissue and suggests that the responses to metformin could be tissue and developmental stage specific [49]. The effect on PDX1 + proliferation induced by metformin was reproduced after treatment with AICAR in vitro , providing strong evidence that this is an AMPK-dependent effect.…”
Section: Discussionsupporting
confidence: 53%
“…In these experiments we present surprising evidence suggesting that metformin increases mTORC1 signaling in embryonic pancreata. This positive effect of metformin has been recently demonstrated in hypothalamic tissue and suggests that the responses to metformin could be tissue and developmental stage specific [49]. The effect on PDX1 + proliferation induced by metformin was reproduced after treatment with AICAR in vitro , providing strong evidence that this is an AMPK-dependent effect.…”
Section: Discussionsupporting
confidence: 53%
“…They concluded that if glucosuria reduction per se could explain the increase in body weight induced by sulfonylureas in diabetic patients, additional mechanisms, such as reduction in food intake and/or increase in EE, might account for the reduction in body weight induced by metformin. Previous studies failed to detect any enhancing effect of metformin on EE . On the contrary, and in accordance with previous studies , we show that metformin transiently reduces EE in WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies failed to detect any enhancing effect of metformin on EE . On the contrary, and in accordance with previous studies , we show that metformin transiently reduces EE in WT mice. In our hands, this EE reduction was equivalent to the caloric content of 300 mg of food, which led to a net effect of metformin‐induced anorexia on energy balance, consistent with the body weight reduction observed in patients under chronic metformin treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The phosphorylation of AMPK and Akt was measured as previously described [20]. The liver and skeletal muscle were quickly dissected and the tissue was homogenized and lysed with radioimmunoprecipitation assay buffer (1.25% Triton X-100, 0.1% sodium dodecyl sulfate, 50mM Tris-HCl, 150mM sodium chloride, 5mM EDTA, pH 7.6) containing a mixture of phosphatase inhibitors, sodium fluoride (Sigma-Aldrich, St. Louis, MO, USA), and sodium pyrophosphate decahydrate (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%